Kepuasan Pernikahan Berhubungan dengan Kecenderungan Berselingkuh - Vivi Amalia (Jurnal Ilmu Perilaku, 2017)
The purpose of this study is to find out the relationship between marital satisfaction and tendency in infidelity among husbands and wives who live in Jabodetabek. The samples of this research are 43 males and 41 females between the ages of 27 and 56 years. The datas were analized using pearson correlation. The results showed that there are a relationship between marital satisfaction and emotional, and emotional physical infidelity. Interpersonal relationship, mutual interest, congruency between role and hope, relationship with in laws, and power and attitudes toward marriage are the domains of marital satisfaction which have a significant relationship with emotional infidelity. The domains mutual interest, relationship with in laws, and power and attitudes toward marriage found have a significant relationship with emostional physical infidelity. Among all those domains, relationship with in laws has more contribution affected tendency in infidelity.